Metod för urval av bäriga bestånd längs med bäriga vägar i Sveaskogs planeringsområde Råneå och Överkalix - Hagström, Dan (2007)
With increased need for flexibility in timber deliveries, forest roads become an important factor. The disintegration of roads during the spring season can be avoided if it is possible to rule cutting areas to stands with good carrying capacity along roads with good carrying capacity. The goal with this work was to create a method to find the stands with high carrying capacity located near roads with high carrying capacity, and select them into a collection file. The method was based on Esri ArcGIS 9 and the tables that follow within that program. The method resulted in four different themes: 1. Collections with GYL 100 that cross the bufferzon for 0, 1, 2 and 3 class roads. Result 36 collections. 2. Collections with GYL 100 and 200 that cross the bufferzon for 0, 1, 2 and 3 class roads. Result 450 collections. 3. Collections with GYL 100 that cross the bufferzon for 0, 1 and 2 class roads. Result 22 collections. 4. Collections with GYL 100 and 200 that cross the bufferzon for 0, 1 and 2 class roads. Result 267 collections. With the attribute table and the tool statistics, different facts for the stands was extracted such as total volume, average volume, site productivity, average age and so on. The results of the analysis showed, however, that many of the collections had restrictions that had made clear cuttings expensive. This investigation should be followed by comparisons in the future to see if the collections with high carrying capacity, near roads with high carrying capacity, has been reduced or increased. Skogsbilvägar blir allt viktigare i skogsbruket med ökat behov av större flexibilitet i leveranser. Stillestånd p.g.a. sönderkörda vägar under våren kan undvikas om man kan styra om avverkningarna till bäriga och vägnära bestånd. Målet med detta arbete har varit att skapa en metod att söka fram vägnära och tillgängliga bestånd ur ett beståndsregister. Metoden går ut på att använda Esri ArcGIS 9 och dess tematabeller till att sortera fram bestånd med önskade egenskaper från ett beståndsregister. Med ...